Biological Activities of Some New Molecular Adducts of Triphenyltin Pseudohalides - Srivastava, T.N.; Srivastava, Shekhar (Asian Journal of Chemistry, 2010)
Some new molecular adducts of triphenyltin pseudohalides of the general formula Ph3SnX.L (X═NCS, NCO) with several O, N, S-donor bases have been synthesised by the direct interaction of pseudohalides Lewis bases either in a suitable solvent or without it. All these compounds have been evaluated for their antibacterial, fungicidal and insecticidal activity. These compounds have also been tested for their in vivo and in vitro (monoamine oxidase and acetylcholinesterase) CNS activity.